THE DIFFICULTIES OF TEACHING ENGLISH TO THE TAIWANESE STUDENTS - Parlindungan, Silalahi Wolter; RIA, Sitorus Friska (PEOPLE: International Journal of Social Sciences, 2015)
The objective of this paper is to investigate the difficulties of teaching English to the Taiwanese Students of Cram School (Buxiban) and the way to solve the difficulties of teaching English to the students. The limitation of this study is on the classroom realities in teaching English as a Foreign Language at Cram School (Buxiban). The participant of this research is the teacher of Cram School (a native speaker from England). This research is a descriptive qualitative research. The difficulties faced by the teachers in teaching English derive from the teacher himself, the students and Cram school (Buxiban). Those difficulties are Mother Tongue Use of the teacher, Mix Ability, Lack of Motivation, Continuity, Taiwan's exam culture, Buxiban (Cram School) materials, Monologue rather than dialogue. The ways to solve those difficulties are the use of Experience, Reflection and Creativity, and the rules on the classroom realities.